The influence of labor education participation on the subjective well-being of college students: chain mediation effect of self-efficacy and healthy lifestyle - Qiu, Danwen; Ni, Jianchao; Yang, Jiaqi (Frontiers in Psychology, 2023)
Background In the process of modernization, along with economic development, intensified social competition, and increasing mental health problems such as anxiety and depression, the issue of subjective well-being has received widespread attention. The level of subjective well-being of college students also affects whether society can achieve sustainable development. In philosophy, political science, economics, sociology and other disciplines, labor is regarded as an important factor affecting subjective well-being. Labor education is an educational activity carried out by Chinese universities in recent years. This further inspires the author to think, for the college students, will the labor education received on campus have an impact on the subjective well-being? What characteristics will its impact mechanism present? What are the characteristics of the influence on subjective well-being?. Methods This research adopts a cross-sectional design, specifically employing a random sampling approach. In this study, the questionnaire was distributed to the college’s students of 14 universities in China through the Internet. A total of 2100 questionnaires were collected. Results This paper mainly used questionnaires to collect data, and on this basis, examined the relationship between labor education participation, self-efficacy, healthy lifestyle and subjective well-being of college students. The results showed that: (1) Labor education participation positively affected college students’ subjective well-being. (2) Self-efficacy partially mediated the relationship between labor education participation and college students’ subjective well-being. (3) Healthy lifestyle partially mediated the relationship between labor education participation and college students’ subjective well-being. (4) Self-efficacy and healthy lifestyle played a chain mediating role between labor education participation and college students’ subjective well-being.